Political and Institutional Transition, Good Governance, and Transitional Justice in Post-Revolutionary Tunisia - Sania Zehraa; Muhammad Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The upheavals in the countries of North Africa and the Middle East turned the region into a global focal point in recent years. The Arab Spring, the conflict between Israel and Palestine, and the development of political ideologies are amongst the key issues in international politics. Currently the Middle East and North Africa is engulfed in an unprecedented outburst of popular protests and demand for reform. The study analyzes the opportunities that emerged when the Arab uprisings were conceptualized as moments of transformation rather than as emerging transitions to democracy. Highlighting critical issues that cut across and link the experiences of political relevant elites and mobilized publics in the cases of Egypt, Libya, Tunisia, and Yemen, it identifies three sets of issues that certified further comparative research: the patterns of state-society relations on the trajectory of Arab uprisings; the role of identity politics and non-state forms of solidarity as drivers of political mobilization and collective action, and the impact of these forms of collective actions on possibilities for establishing stable, legitimate forms of governance; the limits of civil societies and the role of leadership in influencing transitional processes.